Disconnectome associated with progressive white matter hyperintensities in aging: a virtual lesion study - Li, Meng; Habes, Mohamad; Grabe, Hans; Kang, Yan; Qi, Shouliang; Detre, John A. (Frontiers in Aging Neuroscience, 2023)
Objective White matter hyperintensities (WMH) are commonly seen on T2-weighted magnetic resonance imaging (MRI) in older adults and are associated with an increased risk of cognitive decline and dementia. This study aims to estimate changes in the structural connectome due to age-related WMH by using a virtual lesion approach. Methods High-quality diffusion-weighted imaging data of 30 healthy subjects were obtained from the Human Connectome Project (HCP) database. Diffusion tractography using q-space diffeomorphic reconstruction (QSDR) and whole brain fiber tracking with 107 seed points was conducted using diffusion spectrum imaging studio and the brainnetome atlas was used to parcellate a total of 246 cortical and subcortical nodes. Previously published WMH frequency maps across age ranges (50’s, 60’s, 70’s, and 80’s) were used to generate virtual lesion masks for each decade at three lesion frequency thresholds, and these virtual lesion masks were applied as regions of avoidance (ROA) in fiber tracking to estimate connectivity changes. Connections showing significant differences in fiber density with and without ROA were identified using paired tests with False Discovery Rate (FDR) correction. Results Disconnections appeared first from the striatum to middle frontal gyrus (MFG) in the 50’s, then from the thalamus to MFG in the 60’s and extending to the superior frontal gyrus in the 70’s, and ultimately including much more widespread cortical and hippocampal nodes in the 80’s. Conclusion Changes in the structural disconnectome due to age-related WMH can be estimated using the virtual lesion approach. The observed disconnections may contribute to the cognitive and sensorimotor deficits seen in aging.